Pengaruh Variasi Tegangan Input Koil dan Jenis Busi terhadap Daya dan Torsi di Sepeda Motor 110 CC - Elmusyafa’, Muchammad Sabath; Purwoko, Purwoko (MASALIQ, 2024)
The development of the automotive industry is now experiencing a very rapid increase type of motorcycle. One of them is a motorcycle with a transmission with DC ignition. Motorcycle users often experience a lack of performance when used in daily travel. Coil input voltage and spark plug type are the main factors for the lack of performance of the motorcycle, which is less efficient for its users. efficient for its users. The method used in this research is experimentation. Testing conducted using a dynotest tool to find out the comparison of the results of the variables carried out and compared to get the maximum power and torque. The data obtained will be analyzed using statistical methods to eval__uate the relationship between variations in voltage and spark plug type to power and torque. The results of this study showed that the maximum power was obtained from a standard spark plug of spark plug at 8.30 HP at a voltage of 13.5V, the maximum power of iridium spark plugs, spark plugs amounted to 8.57HP at a voltage of 13.5V, and the maximum power of the double iridium spark plugs spark plugs amounted to 8.33HP at a voltage of 13.5V. from the three variations of spark plugs at above the maximum power is obtained at a voltage of 13.5V, and the weakest power is obtained at a voltage of 12V at a voltage of 12V.